2013
DOI: 10.2174/157016113804547629
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal and Spatial Distribution of Macrophage Subpopulations During Arteriogenesis

Abstract: Chronic arterial occlusion leads to growth of collaterals - a process termed arteriogenesis, in which macrophages play a prominent role in remodelling and growth. However, a detailed analysis which of distinct macrophage subpopulations involved in arteriogenesis has never been performed. In the present study the temporal and spatial distribution of macrophage subtypes during arteriogenesis in a rat model with chronically elevated fluid shear stress (FSS) is investigated. Local macrophage subpopulations were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 0 publications
3
61
0
Order By: Relevance
“…This latter study also reported increasing levels of an M2 marker, Chi313 , which is in agreement with our study in which we found increasing levels of the M2 markers Arg1 and CD163. Thus, although we and others found a lack of correlation between iNOS (M1) expression and fibrous capsule thickness, it is likely that macrophages with a predominantly M1 phenotype still contribute to the foreign body response, since persistent levels of M1 macrophages were observed over time, whereas they typically diminish over time in normal wound healing [7, 51]. In addition, both M1 and M2 macrophages secrete factors implicated in the formation of the fibrous capsule, including M1-secreted tumor necrosis factor-α (TNFα) [52] as well as M2-secreted platelet derived growth factor (PDGF) and transforming growth factor-β (TGF-β) [10, 20, 53].…”
Section: Discussionmentioning
confidence: 77%
“…This latter study also reported increasing levels of an M2 marker, Chi313 , which is in agreement with our study in which we found increasing levels of the M2 markers Arg1 and CD163. Thus, although we and others found a lack of correlation between iNOS (M1) expression and fibrous capsule thickness, it is likely that macrophages with a predominantly M1 phenotype still contribute to the foreign body response, since persistent levels of M1 macrophages were observed over time, whereas they typically diminish over time in normal wound healing [7, 51]. In addition, both M1 and M2 macrophages secrete factors implicated in the formation of the fibrous capsule, including M1-secreted tumor necrosis factor-α (TNFα) [52] as well as M2-secreted platelet derived growth factor (PDGF) and transforming growth factor-β (TGF-β) [10, 20, 53].…”
Section: Discussionmentioning
confidence: 77%
“…The contribution of peripheral-derived immune cells during collateral remodeling has recently been demonstrated (la Sala et al, 2012; Troidl et al, 2013). For example, pharmacological monocyte depletion and athymic nude mice that lack T cells display impaired arteriogenesis (Couffinhal et al, 1999; Heil et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Jetten et al also demonstrated that local delivery of 5×10 5 polarized M1 Mø cells (induced by lipopolysaccharide and interferon-gamma) or M2 (induced by IL-4 and IL-10) Mø subsets improved reperfusion recovery in a mouse hind limb ischemia model at day 14, although they did not examine the mechanism involved [29], [30]. Moreover, Troidl et al demonstrated that a forced shift toward M1 and M2 (by intravenous injections of IL-10 or IL-4/IL-13) macrophages improved the arteriogenic response [31]. Thus, the selective methods of culturing and treating M1Mø cells similar to M2Mø cells could be used clinically to help resolve the large number of cells required for BMCs therapy of CLI.…”
Section: Discussionmentioning
confidence: 99%